A SIMULATION STUDY OF STATE-FEEDBACK CONTROL METHOD FOR ELECTRO HYDRAULIC SERVO MODEL - M. H. , Jusoh; Fauzal Naim , Zohedi; Jali, Mohd Hafiz (2013)
Electro hydraulic servo system is used by many industries due to its ability to impart large forces. It also has advantage in term of fast response and robustness. The electro hydraulic system suffered from errors of the transient response which are steady state error, settling time and the ripples. It is crucial to design a controller for the system to ensure the reliability of the system. Aiming at the characteristic of the system, steady state feedback control method is designed to compensate the error. The analysis of the system is done based on the transient response specifically on the actuator part. MATLAB Simulink is used as the simulation software to evaluate the force performance of state feedback controller method. The steady state error, settling time and ripple are observed and recorded for each controller. Three methods is applied, which are full feedback, state feedback with feed forward and integral control are compared with proportional, integral and derivatives (PID) controller. The result of each controller shows the differences performance. Based on the simulation results, the feedforward technique is found to be the best control technique for the electro hydraulic servo system due to the requirement performance such as percent overshoot, settling time, rise time and zero steady state error. This good result will directly benefit industries that use electro hydraulic system as their actuator for production machines.